Seasonal and Storm Event‐Based Dynamics of Dissolved Organic Carbon (DOC) Concentration in a Mediterranean Headwater Catchment - Senatore, Alfonso; Corrente, Giuseppina A.; Argento, Eugenio L.; Castagna, Jessica; Micieli, Massimo; Mendicino, Giuseppe; Beneduci, Amerigo; Botter, Gianluca (Water resources research, 2023)
This study investigates the spatial and temporal dynamics of Dissolved Organic carbon (DOC) concentration in a Mediterranean headwater catchment (Turbolo River catchment, southern Italy) equipped with two multi‐parameter sondes providing more than two‐year (May 2019–November 2021) continuous high‐frequency measurements of several DOC‐related parameters. The sondes were installed in two nested sections, a quasi‐pristine upstream sub‐catchment and a downstream outlet with anthropogenic water quality disturbances. DOC estimates were achieved by correcting the fluorescent dissolved organic matter—fDOM—values through an original procedure not requiring extensive laboratory measurements. Then, DOC dynamics at the seasonal and storm event scales were analyzed. At the seasonal scale, results confirmed the climate control on DOC production, with increasing background concentrations in hot and dry summer months. The hydrological regulation proved crucial for DOC mobilization and export, with the top 10th percentile of discharge associated with up to 79% of the total DOC yield. The analysis at the storm scale using flushing and hysteresis indices highlighted substantial differences between the two catchments. In the steeper upstream catchment, the limited capability of preserving hydraulic connection over time with DOC sources determined the prevalence of transport as the limiting factor to DOC export. In the downstream catchment, transport‐ and source‐limited processes were observed almost equally. The correlation between the hysteretic behavior and antecedent precipitation was not linear since the process reverted to transport‐limited for high accumulated rainfall values. Exploiting high‐resolution measurements, the study provided insights into DOC export dynamics in nested headwater catchments at multiple time scales. Plain Language Summary River networks play a crucial role in the global carbon cycle due to their capacity to process and export terrestrial carbon to the ocean as active pipelines. Most of such exported carbon is dissolved in the water, and a relevant part is organic. This study investigates the dynamics of dissolved organic carbon (DOC) in a Mediterranean headwater catchment equipped with integrated biogeochemical and hydrometeorological sensors. The data collected in an over 2‐year long campaign revealed that even though background values of DOC concentrations are subject to seasonal regulation, up to 80% of the total DOC yield can be associated with 10% of the highest discharge values. Furthermore, the study shows how topographic and climatic characteristics modulate the connectivity between DOC sources and river network, making DOC export processes transport‐limited (i.e., not enough flow is available to mobilize all the stored DOC) or source‐limited (i.e., all the available DOC is mobilized and flushed). The study shed light on the key role of the hydrological cycle in modulating the carbon cycle, quantifying the important cause‐effect nexus. The results contribute to a better understanding of carbon cycling at multiple timescales, providing a clue for the upscaling of carbon export and processing in rivers. Key Points More than two‐year continuous high‐frequency Dissolved Organic carbon (DOC) monitoring in two nested sections with different topographic and land cover features Increasing background concentrations during dry summer, but top 10th percentile of discharge associated with up to 79% of total DOC yield Limiting factors to and evolution of DOC export processes during storms are conditioned by topography and rainfall event features